KEBEBASAN BERAGAMA DAN BERBICARA DALAM BINGKAI KAJIAN TAFSIR NUSANTARA - Miftahul Jannah; Moh Jufriyadi Sholeh (REVELATIA: Jurnal Ilmu Al-Qur'`an dan Tafsir, 2021)
Freedom of belief is one of the human rights that is often discussed in the international community, including freedom of religion. It has been stated in the Quran very clearly that everyone has the freedom to embrace a religion they believe in, beside it has also been explained by Allah that Islam is the most blessed religion. However, there are still forces in choosing a religion in various ways. One of the gifts that Allah has given to humans is freedom of religion based on his own beliefs and freedom of speech. This research focused on how the interpretation of the Archipelago Mufassir about freedom of religion and speech in the al-Qur'an. This study used a qualitative literature approach (Library Research). This type used the thematic analysis method. The primary data source was Tafsir Nusantara, the secondary data was the writer tried to collect data related to the discussion. The results of this study indicated that freedom of religion and speech according to Nusantara Mufassir’s (as Hamka, Quraisy Shihab dan Hasbi Ash-Shidieqy) interpretations towards QS. al-Baqarrah verse 256 that Allah has ordered his people not to force someone to adhere Islam but invite people to think about the truth of Islam. Furthermore, QS. al-Isra' verse 36 implies freedom of speech, it is explained that someone is allowed to speak the truth and not spread lies; a prohibition against talking about something uncertain and to determine something based on personal prejudice and allegation. This verse also prevents from such disadvantages, as accusation, wrong prejudice, lies and false witnesses.